2008
DOI: 10.1148/radiol.2492080304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chest Tomosynthesis and Chest Radiography for Detection of Pulmonary Nodules: Human Observer Study of Clinical Cases

Abstract: For the detection of pulmonary nodules, the performance of chest tomosynthesis is better, with increased sensitivity especially for nodules smaller than 9 mm, than that of chest radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
195
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(209 citation statements)
references
References 33 publications
7
195
2
5
Order By: Relevance
“…Vikgren and colleagues reported on the sensitivity and specificity of DTS as compared with CXR in a similar study completed in 2008 [7]. Analyzing 80 clinically relevant nodules greater than 4 mm, along with 51 smaller nodules, they found that DTS was 56 % sensitive while CXR found only 17 % of the nodules [7].…”
Section: Introductionmentioning
confidence: 99%
“…Vikgren and colleagues reported on the sensitivity and specificity of DTS as compared with CXR in a similar study completed in 2008 [7]. Analyzing 80 clinically relevant nodules greater than 4 mm, along with 51 smaller nodules, they found that DTS was 56 % sensitive while CXR found only 17 % of the nodules [7].…”
Section: Introductionmentioning
confidence: 99%
“…The lateral tomosynthesis scan was performed using the VolumeRad software. The tomosynthesis system and its principles have been described in detail previously [7,8,18,19]. Briefly, 60 low-dose exposures by the moving X-ray tube from tube angles -15 degrees to +15 degrees on a stationary detector are used to reconstruct about 60 tomographic sections of arbitrary thickness.…”
Section: Radiography and Tomosynthesismentioning
confidence: 99%
“…The technique has previously been evaluated in mainly chest radiography [8][9][10] and mammography [11], but has also been applied in abdominal imaging [12] and in musculoskeletal radiography. In a pilot study on scaphoid fracture detection at the two-weeks' follow-up of suspect occult fracture [13], radiography detected one scaphoid waist fracture not detected at radiography at the time of the trauma, while tomosynthesis detected this fracture and two additional fractures, not seen with radiography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital tomosynthesis (DT) combines the benefits of digital imaging [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] with the tomographic benefits of computed tomography. The DT approach can be easily implemented in conjunction with radiography at reduced radiation doses and cost.…”
Section: Introductionmentioning
confidence: 99%